Transformasi cetak ke jurnalisme digital - Andi Dirga Nurhaq; Khairunnisa’ Massang (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2025)
The transformation from print to digital media has changed the way information is disseminated and the interaction between media and audiences. This research aims to analyze the transformation process carried out by Herald.id, iNews, and Ujung Jari, as well as the strategies applied in managing digital content. In addition, this research also identifies the challenges and opportunities that arise in digital journalism and its impact on the audience's news consumption patterns. Using a qualitative approach, this research explores in depth how subjects interpret and understand the change from print to digital media, including their experiences, feelings and perspectives. The results show that while there are significant challenges, there are also great opportunities for innovation that can advance journalism in the digital era.. Keywords: (Transformation Media, Digital Journalism, Adaptation Strateg)